Protein Purification Protocols - Cutler, Paul.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
In this new edition of the very successful Protein Purification Protocols (1996), Paul Cutler completely updates the existing protocols to reflect recent advances and adds an enormous new array of proteomic techniques for protein isolation and analysis. These cutting-edge techniques include not only two-dimensional gel electrophoresis for analysis and characterization, but also analytical chromatography for multidimensional separations of proteins and peptides, and mass spectrometry for isolating proteins. With the many recent advances in technology, simple spectrometric detection is no longer the only option for separating proteins, and the authors treat in full detail all the newer methods for these separations. Comprehensive and highly practical, Protein Purification Protocols, Second Edition, brings together all the key methodologies that both novice and experienced investigators need to carry out successful experimental work on proteins and their functions today.
General Strategies -- Preparation of Extracts From Animal Tissues -- Protein Extraction From Plant Tissues -- Extraction of Recombinant Protein From Bacteria -- Protein Extraction From Fungi -- Subcellular Fractionation of Animal Tissues -- Subcellular Fractionation of Plant Tissues -- The Extraction of Enzymes From Plant Tissues Rich in Phenolic Compounds -- Avoidance of Proteolysis in Extracts -- Concentration of Extracts -- Making and Changing Buffers -- Purification and Concentration by Ultrafiltration -- Bulk Purification by Fractional precipitation -- Ion-Exchange Chromatography -- Hydrophobic Interaction Chromatography -- Affinity Chromatography -- Dye-Ligand Affinity Chromatography -- Lectin Affinity Chromatography -- Immunoaffinity Chromatography -- Immobilized Metal-Ion Affinity Chromatography -- Chromatography on Hydroxyapatite -- Thiophilic Affinity Chromatography and Related Methods -- Affinity Precipitation Methods -- Isoelectric Focusing -- Chromatofocusing -- Size-Exclusion Chromatography -- Fast Protein Liquid Chromatography -- Reversed-Phase Chromatography of Proteins -- Extraction of Membrane Proteins -- Removal of Detergent From Protein Fractions -- Purification of Membrane Proteins -- Lyophilization of Proteins -- Storage of Pure Proteins -- Electroelution of Proteins From Polyacrylamide Gels -- Electroblotting of Proteins From Polyacrylamide Gels -- Two-Dimensional Polyarcylamide Gel Electrophoresis for Proteome Analyses -- Microscale Solution Isoelectrofocusing -- Practical Column Chromatography -- Detection Methods -- Peptide Proteomics -- Multidimensional Liquid Chromatography of Proteins -- Mass Spectrometry -- Purification of Therapeutic Proteins -- Purification Process Scale-Up.
Keywords: Biochemistry; Biochemistry, general